The Application of Constructivism Theory in Moral Learning to Internalize Progressive Islamic Values in Muhammadiyah Elementary Schools - Ayu Rizkia Silviana; Ruwandi (Journal of Cultural Relativism (JCR), 2025)
This study examines the implementation of constructivism theory in moral learning to internalize progressive Islam's values at SD Muhammadiyah Suruh, Semarang Regency. The research method used is qualitative with a case study approach. This research aims to gain an in-depth understanding of pedagogical practices. Data was collected through in-depth interviews with Islamic Religious Education teachers and principals, participatory observation in the classroom to observe teacher interactions and methods, and documentation analysis of Learning Implementation Plans (RPP), teaching modules, and school programs. Data validity was established through source triangulation and confirmation with respondents. The results indicate that implementing constructivism encourages active, participatory, and contextualized moral learning. Methods such as values discussion, role simulation, and Problem-Based Learning (PBL) are applied to facilitate students to solve real moral problems. In addition, reflective activities such as daily moral journals and explicit integration of the values of Islam Berkemajuan significantly deepen the internalization of values. Despite some challenges, such as teachers' lack of understanding of constructivism methods and limited facilities, this study highlighted effective concrete solution strategies, including continuous teacher training, development of specific morals assessment rubrics, utilization of relevant but straightforward learning media, and initiation of collaborative programs between school and parents to integrate education at home. The findings conclude that the constructivism approach, supported by the implementation of strategic solutions, effectively contributes to the formation of student characters who are noble and responsive to the challenges of the times by the ideals of progressive Islamic education.